Modeling and Characteristics Investigation of Warehouse Business Processes in a Clothes Clean&Rental Company - Tadeusz NOWICKI; Robert Waszkowski (Communications of International Proceedings, 2021)
The paper presents results of studies on modeling and characteristics investigation of business processes in a clothes clean&rental company warehouse. Business processes are mainly related to the activity of warehouse employees. Business process models are discussed and presented in the form of ARIS diagrams. Warehouse processes are aimed at streamlining and systematizing the activities carried out as part of warehouse management of workwear in Zwolen (Poland). Warehouse processes have been optimized and designed in accordance with standard procedures performed in the warehouse. The following models of business processes were developed: Demand for Clothing, Taking Clothes into the Warehouse, Order to the Warehouse. Times and costs of task execution were assigned to individual activities in business process diagrams. The times are of stochastic nature. Event attributes in diagrams were also defined. Control flows in the diagrams are determined in accordance with the previously tested probability distributions. Authors conducted simulation of business processes in the ARIS environment and collected results. Then, based on simulation experiments, dynamic characteristics of warehouse activity (in relation to personal resources, times and costs) were determined and presented.
Keywords: Business Process Management; Business Process Modeling; Warehouse processes; Process Simulation; Efficiency